2015
DOI: 10.1016/j.aca.2015.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the oxidase like activity of nanoceria and its application in colorimetric assays

Abstract: Nanomaterial-based enzyme mimics have attracted considerable interest in chemical analysis as alternative catalysts to natural enzymes. However, the conditions in which such particles can replace biological catalysts and their selectivity and reactivity profiles are not well defined. This work explored the oxidase like properties of nanoceria particles in the development of colorimetric assays for the detection of dopamine and catechol. Selectivity of the system with respect to several phenolic compounds, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…The redox reactivity of nanoceria is related to the extent of particle aggregation. For example, nanoceria aggregates have been characterized by negligible activity, while nanoceria dispersions exhibit maximum catalytic activity . It is also known that ssDNA molecules facilitate stabilization and dispersion of nanomaterials .…”
Section: Resultsmentioning
confidence: 99%
“…The redox reactivity of nanoceria is related to the extent of particle aggregation. For example, nanoceria aggregates have been characterized by negligible activity, while nanoceria dispersions exhibit maximum catalytic activity . It is also known that ssDNA molecules facilitate stabilization and dispersion of nanomaterials .…”
Section: Resultsmentioning
confidence: 99%
“…[29][30] These experiments demonstrate that coating of nanoceria affects the reactivity and surface properties of these particles. This property could be used to design sensing schemes based on reactivity changes at the surface of these particles, as we have demonstrated in our recent work for detection of dopamine [31] and phosphatase activity [32] or, for label free detection of clinical and food analytes when used in conjunction with biomolecular recognition elements. [27b, 33] As an example, this assay could be used to detect dopamine and catechol, by measuring the decrease of TMB oxidation with varying concentrations, as shown in Figure 9B and D. These results demonstrate that it is possible to modulate nanoceria reactivity, to either activate, or inactivate chemical reactions at the surface.…”
Section: Effect Of Surface Complexation On Nanoceria Reactivitymentioning
confidence: 99%
“…[17] Asati et al [31] pointed out that nanoceria with smaller size and thinner coating could have higher activity, and this kind of activity would be decreased while the pH increased. Hayat et al [53] found the oxidase mimetic activity was also based on the particle type and buffer ionic strength. They showed the nanoceria with the size of <30 nm and higher zeta potential values would exhibit higher activity, and the higher buffer ionic strength resulted in lower activity, indicating the importance of the particle stability.…”
Section: Mechanisms Of Nanoceria As Oxidase Mimeticsmentioning
confidence: 99%
“…They also tested the oxidase mimetics of different types of nanoceria, and found the oxidase mimetic activity was a common feature for different nanoceria, but varied with the particle size and Zeta potential. [53] …”
Section: Mimetics Of Oxidasesmentioning
confidence: 99%